Computational study of an InGaN/GaN nanocolumn light-emitting diode - Boecklin, Christoph; Veprek, Ratko G.; Steiger, Sebastian; Witzigmann, Bernd (Physical Review B, 2010)
A comprehensive three-dimensional analysis of the operation of an In0.4 Ga0.6 N/GaN nanocolumn light-emitting diode is presented. Focus is put on the investigation of the nature and location of the emitting states. Calculations of strain and polarization-induced internal fields show that the strong lateral dependence of the potential gives rise to states confined to the periphery and to the center of the nanocolumn. However, lateral confinement of states near the column center is weak such that a quantum-well-like treatment of the remaining bound states seems appropriate where coherence is lost in the lateral directions. Within this picture, a coupled and self-consistent three-dimensional simulation of carrier transport and luminescence is presented, thus accounting for screening and lateral transport effects. Results are compared to a planar quantum-well device. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2021-06-11